Chemical composition and antiproliferative, antioxidant and trypanocidal activities of the fruits from Campomanesia xanthocarpa (Mart.) O. Berg (Myrtaceae) - Salmazzo, Gustavo Ruivo; Verdan, Maria Helena; Silva, Flávia [UNESP]; Cicarelli, Regina Maria [UNESP]; Mota, Jonas da Silva; Salvador, Marcos José; de Carvalho, João Ernesto; Cardoso, Cláudia Andrea Lima (Taylor & Francis, 2019)
Chemical investigation of the extracts of the fruits from Campomanesia xanthocarpa resulted in the isolation of six known compounds identified by NMR and comparison with literature data (2′,4′-dihydroxy-5′-methyl-6′-methoxychalcone (1), 2′,4′-dihydroxy-3′,5′-dimethyl-6′-methoxychalcone (2), 2′-hydroxy-3′-methyl-4′,6′-dimethoxychalcone (3), 2′,6′-dihydroxy-3′-methyl-4′-methoxychalcone (4), 5-hydroxy-7-methoxy-8-methylflavanone (5) and 7-hydroxy-5-methoxy-6-methylflavanone (6)). The considerable antioxidant capacity of the extracts was demonstrated by ORAC-FL and DPPH tests. The antiproliferative assay of the extracts and 5 was done in vitro, against many different cancer cell lines besides a healthy one. The extracts presented low cytotoxicity and the substance demonstrated promising results against all the cancer cell lines tested, with IC 50 values ranging from 4.75 to 45.81 µmol L −1 . The in vitro trypanocidal activity was evaluated against the epimastigote form of the Y strain of Trypanosoma cruzi and an improvement in the activity of the substances 2 (221.81 µmol L −1 ) and 5 (61.87 µmol L −1 ) was observed regarding the values obtained for the extracts.
Keywords: Campomanesia xanthocarpa; chalcones; flavanones; guavira; Trypanossoma cruzi